Development of Wireless Electric Field Mill for Atmospheric Electric Field Observation - Muhammad Abu Bakar Sidik; Hamizah Shahroom; Zolkafle Buntat; Yanuar Zulardiansyah Arief; Zainuddin Nawawi; Muhammad Irfan Jambak (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2014)
Rotating-vane electric field mill (REFM) sensor is one of the popular methods to measure atmospheric quasi-static electric field. Lightning incident occasion can be predicted by observing electric fields strength in atmosphere. In this paper an integration of REFM with an online wireless data monitoring system for long distance observation and data collection is presented. This method reduces the required man-hour to gather data from the REFM as well as system costs by removing the computer and data logger on-site. The development includes hardware and software design in order to improve efficiency the atmospheric electric field measurement system. The contribution of this work is the design of the electronic circuit which converts the ac signal from the REFM sensor to dc signal and then correlates the signal to the electric field strength in the vicinity. Subsequently the information is transmitted via a wireless data transmission system, using the Global System Mobile Communication (GSM) network. Using the proposed method, all the data from sensors can be observed and analysed immediately from any location.